2017
DOI: 10.3390/polym9050173
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Application of Four Novel Electrochromic Materials Employing Nitrotriphenylamine Unit as the Acceptor and Different Thiophene Derivatives as the Donor

Abstract: Abstract:In this study, four novel donor-acceptor systems, 4-(2,3-dihydrothieno [3,4-b]and 4-nitro-N,N-bis(4-(thiophen-2-yl)phenyl)aniline (NTTPA), were successfully synthesized by Stille coupling reaction and electropolymerized to obtain highly stable conducting polymers, PNETPA, PNMOTPA, PNMTPA and PNTTPA, respectively. The polymers were characterized using cyclic voltammetry (CV), step profiling and UV-Vis-NIR spectroscopy. The band gaps (E g values) were 1.34, 1.59, 2.26, and 2.34 eV, for PNETPA, PNMOTPA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Here, Q is the amount of charge transferred per unit area. The calculated optical density Δ OD = 0.76 and the amount of charge Q = 0.01451 C.cm −2 leads to a coloration efficiency value of 52.4 cm 2 ·C −1 The rather low CE value as compared to the ones reported in the literature [1,14,15,17] may originate from the wide potential range leading to large current values measured using chronoamperometry while the capacity is usually deduced from dynamic measurements using cyclic voltammetry.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Here, Q is the amount of charge transferred per unit area. The calculated optical density Δ OD = 0.76 and the amount of charge Q = 0.01451 C.cm −2 leads to a coloration efficiency value of 52.4 cm 2 ·C −1 The rather low CE value as compared to the ones reported in the literature [1,14,15,17] may originate from the wide potential range leading to large current values measured using chronoamperometry while the capacity is usually deduced from dynamic measurements using cyclic voltammetry.…”
Section: Resultsmentioning
confidence: 89%
“…The list of electrochromic materials include inorganic systems (e.g., WO 3, V 2 O 5, NiO [7,8,9] and Prussian blue [10]) and organic ones (e.g., viologens, polyaniline, and poly(3,4-ethylenedioxythiophene)). Compared with inorganic electrochromic materials, organic electrochromic materials have advantages such as a broader color palette, higher coloration efficiency, and greater optical contrast [11,12,13,14,15,16]. In addition, recent studies have demonstrated the suitability of a large number of techniques, including spray coating, ink jet, and doctor blading, for deposition of thin films of conducting polymers with good control of the process [17,18,19,20,21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] In addition, al arge number of TPA-based polymers exhibit electrochromic behaviord uring redoxp rocesses that have potential applications in ECDs. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] To improve the charge carriert ransport properties and structural stabilities of polymerc hains, somet hiophene derivatives, such as 2,2'-bithiophene and 3,4-ethylenedioxythiophene (EDOT), have been incorporated within the polymer backbonea s" bridge" linkages. As eries of monomers that consist of aT PA core substituted by thiophene derivatives was synthesized recently,a nd the resulting polymers possess good electrochemical stabilitya nd variouse lectrochromic properties.…”
Section: Introductionmentioning
confidence: 99%
“…As eries of monomers that consist of aT PA core substituted by thiophene derivatives was synthesized recently,a nd the resulting polymers possess good electrochemical stabilitya nd variouse lectrochromic properties. [31][32][33][34][35][36] One of these reported monomers is tris [4-(3,4-ethylenedioxythiophene)phenyl]amine (TEPA), which was synthesized by the Stille cross-coupling reaction. [31,37] Chahma et al [37] and Idzik et al [38] prepared poly-{tris [4-(3,4-ethylenedioxythiophene)phenyl]amine} (PTEPA) films by electrochemical polymerization andf ound that they have significant electroactivity and reasonable redox stability,a lthought hese films are insoluble in all common solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation